Effect of Information Technology Capability On Competitive Advantage of the Kenyan Banking Sector - Kamau, James Gathogo; Senaji, Thomas A.; Nzioki, Susan (IPRJB, 2019)
Purpose: The study sought to establish the effect of Information Technology Capability on competitive advantage of the banking sector in Kenya. Methodology: The study is anchored on the McKinsey 7S Framework Model and the dynamic capability Theory. A positivist research philosophy was adopted for the study. Focusing on 39 operational commercial banks in Kenya, a descriptive survey design was adopted. Primary data was collected and applied in the study. Findings: The relationship between the variables was tested using ordinary east square regression model. The study findings revealed that strategic capabilities, that is information technology capability have a positive and significant effect on competitive advantage of commercial banks in Kenya. Unique contribution to theory, practice and policy: The study findings led to the recommendation that the commercial banks should enhance the practices that improves their strategic capabilities
Keywords: Information Technology Capability; Commercial Bank and Competitive Advantage